Eduard Meyer : Leben und Leistung eines Universalhistorikers - Calder, William M. 1932-; Demandt, Alexander, 1937- (Mnemosyne, Supplements, 1990)
Eduard Meyer (1855-1930) was among the most important historians of his age. After Mommsen he is the best known German ancient historian. From 1902 he taught ancient history in Berlin and from 1919/20 he was vice-chancellor. His most important work \'Geschichte des Altertums\' includes the ancient oriental cultures, contains a sociological- anthropological methodology and considers all humane studies, especially religious history. This collection treats aspects of Meyer's biography - including his journey to America, his relations with his contemporaries (M. Weber, O. Spengler, U.von Wilamowitz), his university politics, his role in the First World War, his positions on Christianity and Judaism, history of philosophy, and particular research results and their effect.